Respuesta :

Answer:

43

Step-by-step explanation:

Using the remainder theorem, that is

The remainder on dividing f(x) by (x - h) is the value of f(h)

here division by (x - 3) hence evaluate f(3) for remainder

f(3) = 3² + 14(3) - 8 = 9 + 42 - 8 = 43 ← remainder

As per the remainder theorem, a polynomial P(x) is divided by (x-t) then the remainder is equal to P(t). When f(x) = x2 + 14x − 8 is divided by (x − 3), the value of the remainder is 43. The correct option is A.

What is the Remainder theorem?

According to the remainder theorem, when a polynomial P(x) is divided by (x-t) then the remainder of the division is equal to P(t). If P(t)=0, then the (x-t) is the factor of the polynomial.

We can find the value of the remainder, when f(x) = x² + 14x − 8 is divided by (x − 3) by using the remainder theorem.

Now, as per the remainder when f(x) = x² + 14x − 8 is divided by (x − 3) will be equal to f(3). Therefore, the value of the remainder will be,

f(x) = x² + 14x − 8

f(3) = (3)² + 14(3) − 8

     = 9 + 42 - 8

     = 43

Hence, when f(x) = x2 + 14x − 8 is divided by (x − 3), the value of the remainder is 43.

Learn more about the Remainder Theorem here:

https://brainly.com/question/13264870

#SPJ5